Free-Base Porphyrin Aggregates Combined with Nickel Phosphite for Enhanced Alkaline Hydrogen Evolution - Bogdan-Ovidiu Taranu; Eugenia Fagadar-Cosma; Paula Sfirloaga; Maria Poienar (Energies, 2023)
In response to the escalating global energy requests and the need to address them in a sustainable manner, researchers have identified hydrogen as an energy vector that provides a practical way to store and use energy from renewable sources. To make a step forward, the electrocatalytic properties for the hydrogen evolution reaction in an alkaline medium of graphite electrodes modified with combinations of nickel phosphite and free-base porphyrins were investigated voltammetrically. The sample obtained by combining the respective phosphite with 5,10,15,20-tetrakis(4-methoxyphenyl)porphyrin exhibited the highest catalytic activity, surpassing that observed for the specimens manufactured using the individual catalysts and thus providing enhanced water-splitting performance. The best electrode displayed an overpotential of 0.43 V (at i = −10 mA/cm2) and a Tafel slope of 0.14 V/dec. Since the catalytic activity of the compositions containing the metal salt and the porphyrins has not been previously studied, the investigation and its outcome constitute an original contribution to the growing water-splitting literature, providing new opportunities for obtaining better results than the ones reported for electrodes modified solely with the phosphite.